Methanogenic potential of archived soils - Emilia Urbanek (Carpathian journal of earth and environmental sciences, 2014)
Methane (CH4) is an important element of the biogeochemical carbon cycle. Methanogenic Archaea are strict anaerobes able to survive in dry and oxic soils, but not in liquid or agar slurry. Little is known about the mechanisms of their survival. The aim of this paper is to study the methanogenic potential of mineral soils stored as air-dry over 20 years. We tested the hypothesis that the recovery of CH4 formation is strongly associated with soil textures. Samples of 16 mineral topsoils characterized by various Corg, pH and particle size distribution (PSD), and stored under air-dry conditions over 20 years were flooded with: i) water and incubated in N2 atmosphere, or ii) with glucose solution without headspace gas exchange and incubated for 132 days. Gases were measured chromatographically, PSD by laser diffraction method. Microbial activity was restored in all tested soils, and CH4 and CO2 production started within a few days or weeks after flooding, depending on soil properties and incubation conditions. The glucose amendment resulted in a 2.8-fold increase in the total CH4 and CO2 release. However, in the presence of glucose, methanogens in three soils were outcompeted by other microorganisms, and required a long 132-d lag phase or did not start CH4 production at all. The CH4 positively correlated with the finer soil fractions, especially with fine silt and clay, while negatively with medium and coarse sand fractions. Consequently, silt loam soils showed approximately 5 and 2.5 times higher CH4 production, than soils with coarser textures (sand and sandy loam soils, respectively). In contrast, CO2 production was not influenced by soil texture. The Corg andmoisture retention in dry soils showed even stronger correlations with CH4 and CO2, except for CH4 released in the presence of glucose, where correlations with PSD were strongest. Most soil properties were associated with the first principal component (PC1), which explained 58.1% of the qualitative differences between the compared soils. The results stressed the significance of the inherent soil properties in determining the persistence of microorganisms responsible for CH4 and CO2 production over long storage in air-dry conditions. In fact, all analysed soil properties are related to each other and create specific habitats which allow microorganisms to persist in unfavourable conditions. Anaerobic incubations without C amendment resulted in CH4 production in all tested soils, while in some glucose enriched sand or sandy loam soils methanogens were outcompeted by other microorganisms.